"Activated Borane": A Porous Borane Cluster Polymer as an Efficient Lewis Acid-Based Catalyst - Lamač, Martin; Urbán, Béla; Horáček, Michal; Bůžek, Daniel; Leonová, Lucie; Stýskalík, Aleš; Vykydalová, Anna; Škoch, Karel; Kloda, Matouš; Mahun, Andrii; Kobera, Libor; Lang, Kamil; et al. (ACS catalysis, 2023)
Borane cluster-based porous covalent networks, named activated borane (ActB), were prepared by cothermolysis of decaborane(14) (nido-B10H14) and selected hydrocarbons (toluene, ActB-Tol; cyclohexane, ActB-cyHx; and n-hexane, ActB-nHx) under anaerobic conditions. These amorphous solid powders exhibit different textural and Lewis acid (LA) properties that vary depending on the nature of the constituent organic linker. For ActB-Tol, its LA strength even approaches that of the commonly used molecular LA, B(C6F5)3. Most notably, ActBs can act as heterogeneous LA catalysts in hydrosilylation/deoxygenation reactions with various carbonyl substrates as well as in the gas-phase dehydration of ethanol. These studies reveal the potential of ActBs in catalytic applications, showing (a) the possibility for tuning catalytic reaction outcomes (selectivity) in hydrosilylation/deoxygenation reactions by changing the material's composition and (b) the very high activity toward ethanol dehydration that exceeds the commonly used γ-Al2O3 by achieving a stable conversion of ∼93% with a selectivity for ethylene production of ∼78% during a 17 h continuous period on stream at 240 °C.